Frequent mechanical stress suppresses proliferation of mesenchymal stem cells from human bone marrow without loss of multipotency - Frank, Viktoria; Kaufmann, Stefan; Wright, Rebecca; Horn, Patrick; Yoshikawa, Hiroshi Y.; Wuchter, Patrick; Madsen, Jeppe; Lewis, Andrew L.; Armes, Steven P.; Ho, Anthony Dick; Tanaka, Motomu (Scientific reports, 2016)
Mounting evidence indicated that human mesenchymal stem cells (hMSCs) are responsive not only to biochemical but also to physical cues, such as substrate topography and stiffness. To simulate the dynamic structures of extracellular environments of the marrow in vivo, we designed a novel surrogate substrate for marrow derived hMSCs based on physically cross-linked hydrogels whose elasticity can be adopted dynamically by chemical stimuli. Under frequent mechanical stress, hMSCs grown on our hydrogel substrates maintain the expression of STRO-1 over 20 d, irrespective of the substrate elasticity. On exposure to the corresponding induction media, these cultured hMSCs can undergo adipogenesis and osteogenesis without requiring cell transfer onto other substrates. Moreover, we demonstrated that our surrogate substrate suppresses the proliferation of hMSCs by up to 90% without any loss of multiple lineage potential by changing the substrate elasticity every 2nd days. Such “dynamic in vitro niche” can be used not only for a better understanding of the role of dynamic mechanical stresses on the fate of hMSCs but also for the synchronized differentiation of adult stem cells to a specific lineage.